Energy systems functionality test rates: model characteristics for elite ski racers trained for XXIV Olympic Winter Games in Beijing - Golovachev, A. I.; Kolykhmatov, V. I.; Shirokova, S. V.; Novikova, N. B. (Theory and Practice of Physical Culture, 2019)
The article presents, for the first time, the results of development of model characteristics of energy supply systems in highly-qualified racing skiers, the achievement of which underlies the successful performance at the XXIV Olympic Winter Games in Beijing (China) in 2022. Considering the requirements for the formation of model characteristics of female athletes trained for the Olympic Games, we selected 18 indicators to assess the level of physical working capacity, state of the power and economization capabilities of the main energy supply systems (oxidation and lactacid) and acting as a system-forming factor that integrates the functional systems of the body. The study involved 19 female racing skiers from different age groups (from 19 to 27 years) and with different sports experience (from 6 to 13 years). They were all qualified from CMS to WCMS and specialized in various types of competitive activity. The study of the functional capabilities of the female athletes was carried out during the 2015-2018 Olympic cycle under the program of methodological support during the stage-by-stage comprehensive examinations conducted in the laboratory of Olympic cyclic sports of the Federal State Budgetary Institution Federal Science Center for Physical Culture and Sport. The methodological feature of the study was the creation of a structural-functional model (model of Olympic athlete-2022), which includes the indicators that reflect the individual characteristics of development of energy supply systems ensuring effective selection, identification of the degree of readiness to perform specific muscular activity, as well as correction of the training process.